In silico evaluation of snake venom proteins against multidrug-resistant Mycobacterium tuberculosis: A molecular dynamics study and simulation dynamic - Maged Fouda; Mohammad J. S. Mantargi; Mousa O. Germoush; Moustafa Sarhan; Modather F. Husein; Mohamed M. Abdel-Daim (Open Veterinary Journal)
Background: Mycobacterium tuberculosis (Mtb), a pathogen that belongs to the M. tuberculosis complex (MTBC), causes tuberculosis (TB), an infectious bacterial disease. Although it usually affects the lungs and results in pulmonary tuberculosis, it can also lead to extra-pulmonary tuberculosis by affecting other regions of the body. TB, which ranks first on the list of infectious diseases that kill the most people, affects one-third of the world's population and has a high mortality and morbidity rate. The clinical treatment of active TB infection mainly relies on the use of isoniazid INH in combination with three other drugs—rifampin, pyrazinamide, and ethambutol. However, the situation is getting worse due to the rise of extremely drug-resistant tuberculosis (XDR-TB) and multidrug-resistant tuberculosis (MDR-TB). Finding more effective drugs is always a top priority. In this regard, animal venoms, such as snake toxins, contain antibacterial chemicals that have significant therapeutic properties and prevent bacterial infections and disease progression. This suggests that snake venom is a good natural source of promising novel anti-TB drugs.